Analyzing the carbon dioxide emissions of R134a alternatives in water-cooled centrifugal chillers using the life cycle climate performance framework - Akinseloyin, Michael O.; Hall, Carter; Stallbaumer-Cyr, Emily M.; Morrow, Jordan A.; Derby, Melanie M. (Frontiers in Energy Research, 2023)
Introduction: To reduce greenhouse gases, the Kigali Amendment to the Montreal Protocol seeks a phasedown of hydrofluorocarbons. R134a alternatives were analyzed for use in a water-cooled chiller: R450A, R513A, R516A, R1234ze (E), R515A, and R515B. Methods: A thermodynamic model of the chiller was employed to calculate compressor power, an input to the life cycle climate performance (LCCP) framework to estimate total equivalent carbon dioxide emissions, CO2eq. Emissions were calculated for an 809 kW [230 Tons of refrigeration (RT) nameplate] water-cooled centrifugal chiller at constant cooling capacity using five power sources (i.e., coal, distillate fuel oil, natural gas, nuclear, and wind) for a median chiller lifetime of 27 years. Two chiller operating profiles were considered: one using operational data from a university campus and a second from literature based on the Atlantic Fleet operation. Results and discussion: When powered via fossil fuels, over 90% of emissions were due to the indirect emissions from energy; therefore, the global warming potential (GWP) of the refrigerant was not the primary contributor to the total CO2eq emissions. With natural gas, total LCCP emissions were reduced for R450A (7.8%), R513A (4.7%), R516A (9.4%), R1234ze (E) (10%), R515A (8.4%), and R515B (6.4%) compared to R134a for the university campus load profile. For the round-the-clock Atlantic Fleet profile, there were emission reductions for R450A (3.6%), R513A (0.25%), R516A (2.3%), R1234ze (E) (2.4%), R515A (1.5%) and R515B (2.4%) compared to R134a. When coupled with renewable energy, the indirect emissions from the chillers substantially decreased, and GWP-dependent leakage emissions accounted for up to 74% or 40% of emissions from R134a alternatives powered by wind and nuclear, respectively. For operation using the load profile from the university campus chillers, R450A had the highest coefficient of performance (COP) of 5.802, while R513A had the lowest COP (5.606). Tradeoffs between alternative refrigerants exist in terms of operation, temperature glide, size of heat exchangers, system design, flammability, cost, availability, and material compatibility. In terms of flammability, R134a, R513A, R450A, R515B and R515A are A1 (nonflammable) fluids. R450A and R516A also have temperature glides of 0.4 K and 0.056 K, respectively, which can affect condenser design. In terms of equipment modification (sizing), R513A require fewer modifications.